Clinical experience with apremilast for psoriatic arthritis - E. Yu. Loginova; T. V. Korotaeva (Современная ревматология, 2018)
The novel targeted synthetic disease-modifying antirheumatic drug apremilast (AP), a phosphodiesterase 4 inhibitor, is currently used to treat psoriasis and psoriatic arthritis (PsA). AP treatment can reduce the level of proinflammatory cytokines and the activity of inflammatory changes. The article describes a clinical observation of the efficacy of AP in PsA. It is demonstrated that AP used at a dose of 60 mg/day for moderate PsA activity leads to a reduction in the manifestations of peripheral arthritis, psoriasis (both during monotherapy and in combination with methotrexate), as well as to the achievement of low or minimal disease activity. It is shown that AP is generally well tolerated by patients.